Implementation of Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in Recommendations for New Position in Companies - Mesran M; Eka Pratiwi Sumantri; Supriyanto S; Syafrida Hafni Sahir; Nelly Khairani Daulay (IJISTECH (International Journal of Information System and Technology), 2021)
This study aims to provide support to management in recommendations for promotion of employee promotions, with the aim of providing motivation to employees. The problem encountered at this time is the number of employees making it difficult for management to choose employees to recommend in promotions for promotions. In this research, the method used is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) which is a fairly good method in ranking where the best alternative is the alternative that has the closest distance to the best alternative and far from the worst alternative. From the research results, it can be concluded that the A5 alternative is the best with a value of 0.748 and can be recommended in a new position promotion at the company.